A general, concise, 'collective' approach to eudesmanolide sesquiterpenoids: total synthesis of bioactive atractylenolides I–IV and related natural products. Issue 41 (7th October 2015) - Ramesh, Subburethinam; Mehta, Goverdhan
Graphical abstract: Abstract: Total synthesis of seven bioactive atractylenolide-type eudesmanolides from Hagemann's ester, following, a short, scalable, adaptable, and diversity oriented protocol, has been accomplished. This effort opens a gateway to access through synthesis an exceptionally potent and promising group of natural products and their congeners of contemporary interest.